Dosis Pupuk Organik sebagai Faktor Penentu Pertumbuhan dan Produktivitas Jagung Pakan (Zea mays L.) - Karfika Yulia Sari; Lukman Arif; Adnan Adnan (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
This study aimed to determine the effect of various doses of Magau organic fertilizer on the growth and yield of forage maize. The research was conducted in Pangi Village, Baolan District, Tolitoli Regency, Central Sulawesi, from November 2022 to February 2023. The experiment used a Randomized Block Design (RBD) with five fertilizer doses: 0, 25, 50, 75, and 100 g per plant. Data were analyzed using analysis of variance (ANOVA) and followed by the DMRT test to identify significant differences among treatments. The results showed that Magau organic fertilizer significantly affected the number of leaves, ear length, ear diameter, and ear weight, but had no significant effect on plant height and leaf length. The best treatment was obtained with 100 g per plant, which produced optimal growth and yield of forage maize. This study is expected to serve as a reference for farmers in Tolitoli Regency in developing forage maize cultivation using Magau organic fertilizer and as a comparative reference for future research.